2018
DOI: 10.1097/md.0000000000012561
|View full text |Cite
|
Sign up to set email alerts
|

The association of polymorphisms in promoter region of MMP2 and MMP9 with recurrent spontaneous abortion risk in Chinese population

Abstract: This study aimed to reveal the genetic association between polymorphisms in promoter region of matrix metalloproteinase 2 (MMP2) and matrix metalloproteinase 9 (MMP9) and the risk of recurrent spontaneous abortion (RSA) in Chinese population.A total of 129 RSA patients and 116 relative controls were selected and the genotyping of polymorphism was conducted by polymerase chain reaction with sequencing. Genotype distribution of polymorphism in the control group was tested the status of Hardy–Weinberg equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…They agrees with the results of Behforouz et al [23], Pereza et al [27], and Ramu et al [28]. In contrast Li et al [19], showed that the polymorphism rs243865 were significantly associated with an increased susceptibility to recurrent miscarriages.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They agrees with the results of Behforouz et al [23], Pereza et al [27], and Ramu et al [28]. In contrast Li et al [19], showed that the polymorphism rs243865 were significantly associated with an increased susceptibility to recurrent miscarriages.…”
Section: Discussionsupporting
confidence: 90%
“…These observations were similar to the results presented by Li et al, and. Behforouz et al [19,23]. However, not all studies are in consistency with results of the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In almost 50% of RSA cases, however, the underlying cause is unknown; in this case, the condition is known as unexplained RSA (URSA). The treatment for URSA is problematic with no widely accepted therapeutic option, bringing distress to both the affected women and their families . Therefore, it is essential to investigate effective treatments and improve the rate of successful pregnancy in URSA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that susceptibility genes have an important relationship to the pathogenesis of recurrent spontaneous abortion . In recent years, with the increase in research on recurrent abortion, an increasing number of susceptibility genes, such as MMP2, MMP9, CTLA4, FOXP3, and THBD, have been found to be associated with susceptibility to recurrent miscarriage . In addition, studies have confirmed that some genes that regulate cell migration are associated with susceptibility to recurrent miscarriage Studies have also found that long non‐coding RNA (lncRNA) polymorphisms are also associated with recurrent miscarriage.…”
Section: Introductionmentioning
confidence: 99%